Direct Regeneration of Spent Lithium-Ion Battery Cathodes: From Theoretical Study to Production Practice - Huang, Meiting; Wang, Mei; Yang, Liming; Wang, Zhihao; Yu, Haoxuan; Chen, Kechun; Han, Fei; Chen, Liang; Xu, Chenxi; Wang, Lihua; Shao, Penghui; Luo, Xubiao (Nano-Micro Letters, 2024)
Direct regeneration method has been widely concerned by researchers in the field of battery recycling because of its advantages of in situ regeneration, short process and less pollutant emission. In this review, we firstly analyze the primary causes for the failure of three representative battery cathodes (lithium iron phosphate, layered lithium transition metal oxide and lithium cobalt oxide), targeting at illustrating their underlying regeneration mechanism and applicability. Efficient stripping of material from the collector to obtain pure cathode material has become a first challenge in recycling, for which we report several pretreatment methods currently available for subsequent regeneration processes. We review and discuss emphatically the research progress of five direct regeneration methods, including solid-state sintering, hydrothermal, eutectic molten salt, electrochemical and chemical lithiation methods. Finally, the application of direct regeneration technology in production practice is introduced, the problems exposed at the early stage of the industrialization of direct regeneration technology are revealed, and the prospect of future large-scale commercial production is proposed. It is hoped that this review will give readers a comprehensive and basic understanding of direct regeneration methods for used lithium-ion batteries and promote the industrial application of direct regeneration technology. Highlights: 1 This review systematically summarizes the source of electricity, the key choice of catalyst, and the potentiality of electrolyte for prospective hydrogen generation. 2 Each section provides comprehensive overview, detailed comparison and obvious advantages in these system configurations. 3 The problems of hydrogen generation from electrolytic water splitting and directions of next-generation green hydrogen in the future are discussed and outlooked.